The mediating role of self-efficacy in the relationship between social support and work withdrawal behavior: A cross-sectional study among young lung cancer survivors - Jiudi Zhong; Lu Shao; Ziya Xin; Jun-E Zhang (Elsevier, 2023)
Objective: The study aimed to explore the predictors of work withdrawal behavior among young lung cancer survivors and examine the mediating role of self-efficacy in the relationship between social support and work withdrawal behavior. Methods: This cross-sectional study was conducted in a cancer center in southern China. A total of 215 young lung cancer survivors were recruited from January 2021 to July 2021 and investigated by a demographic and disease-related questionnaire, the Work Withdrawal Behavior Scale, Social Support Rating Scale, and General Self-efficacy Scale. Data analysis was performed ​using ​IBM SPSS 25.0 (IBM Corp., Armonk, NY, USA) and PROCESS macro version 3.3 for SPSS developed by Preacher and Hayes. Results: The mean score of work withdrawal behavior was 3.02 (±0.70). Existing symptoms, income, residence, the duration of postoperative rest time, social support, and self-efficacy were the predictors and explained 70.2% of the variance of work withdrawal behavior. The mediating effect of self-efficacy was identified between social support and work withdrawal behavior (indirect effect ​= ​0.36, bias-corrected 95% confidence interval [−0.542 to −0.197]). Conclusions: Work withdrawal behavior was prevalent among young lung cancer survivors. Social support and self-efficacy were significantly associated with work withdrawal behavior, and self-efficacy was identified as a mediator between social support and work withdrawal behavior among this group. Health professionals could help them return and adapt to work by relieving their symptoms, providing social support, and enhancing their self-efficacy.